Efektifitas Metode Pembelajaran Field Trip Pendekatan DFC Mengembangkan Entrepreneurial Leadership Anak Petani Garam - Siti Fadjryana Fitroh; Dewi Mayangsari; Ratna Nila Puspitasari (Trunojoyo University of Madura, 2019)
Experience is part of an important aspect of learning, besides that it needs to be noted that the characteristics of early childhood, the main one is high curiosity supported by imagination. To be able to facilitate it all is needed to provide the right stimulus through the methods and approaches integrated in learning. The form of learning activities is also a determining factor, which is clearly all done in the principle of fun learning and that is in entrepreneurial activities. In every learning that is applied to early childhood it is important to be formed consistently both at home, school and the environment around the residence. In learning also aims at the formation of personal character that is having the soul of leadership. By having these characters, the hope is that the child can later become the successor to the generation that has been tradition in Lembung Village, Galis Subdistrict, Pamekasan Regency, namely Garam entrepreneurs. However, all of that must go through a process, if you want the right end. This study involved 15 group B students at the PKK Lembung Kindergarten, using qualitative methods with sources of data on observation, interviews and documentation. The purpose of this study is to look at the effectiveness of learning using field trip learning methods or tourism works integrated with the DFC approach to salt farmers. The field trip method integrated with the DFC approach in entrepreneurial activities has the aim that the salt farmer's children who already have entrepreneurial leadership provision have more courage, independence, skills so as to minimize failures in themselves, not easily discouraged, continue to struggle and be optimistic.